Performance optimization of industrial scale in-ground lagoon anaerobic digester for palm oil mill effluent (POME) treatment - Mohd Yusof, Mohd Amran (2025)
Despite advancements in treating Palm Oil Mill Effluent (POME) using anaerobic methods, challenges persist in optimising biogas production and effluent treatment due to unpredictable characteristics influenced by palm oil extraction efficiency and mill processes. Recent changes in Malaysia's Feed-In Tariff (FiT) program, particularly the introduction of an e-bidding system have led to reduced average FiT rates, impacting biogas plant developers with high capital expenditure. Additionally, long-term operational challenges in biogas plants require an understanding of POME characteristics and factors influencing anaerobic digestion performance throughout the Renewable Power Purchase Agreement (REPPA) period of 21 years. Therefore, the main objective of this study is to maximise methane yield of the biogas plant through optimisation analysis and assess its feasibility via techno-economic analysis.